Experimental and numerical evaluation of the mechanical behavior of diagonally reinforced plates subjected to the effect of residual thermal stresses (2017)
This paper presents an experimental and numerical study of the effect of residual thermal stresses on the mechanical behavior of diagonally reinforced plates. The study focuses on the analysis of carbon/epoxy square plates onto which diagonal reinforcements were glued. These reinforcements were glued using two different methodologies: the first method was to glue the reinforcements at operating temperature (22 °C), while in the second methodology reinforcements were cured in an autoclave at 177 °C. Mechanical behavior assessment was based on the stiffness, free vibration, and buckling tests. For the study of the stiffness of the plates, an optical technique to determine the transversal displacement caused by the presence of a static load was employed. For the vibration tests, the natural frequencies associated with the first four modes of free vibration were determined by using a dynamic signal analyzer. For the linear and non-linear buckling, compression tests on a universal testing machine were performed, determining the displacements produced during the test using the digital image processing method. All experimental results were compared with results obtained from numerical approximations made with commercial software. The results show the effect of residual thermal stresses caused during the manufacturing process on the mechanical performance of diagonally reinforced plates.